Genetic diversity and sex‐biased dispersal in the brown spotted pitviper (Protobothrops mucrosquamatus): Evidence from microsatellite markers. Issue 3 (1st March 2022) - Yu, Min; Liu, Qin; Wu, Ya‐Yong; Guo, Peng; Yang, Kong
Abstract: Dispersal plays a vital role in the geographical distribution, population genetic structure, quantity dynamics, and evolution of a species. Sex‐biased dispersal is common among vertebrates and many studies have documented a tendency toward male‐biased dispersal in mammals and female‐biased dispersal in birds. However, dispersal patterns in reptiles remain poorly understood. In this study, we explored the genetic diversity and dispersal patterns of the widely distributed Asian pitviper Protobothrops mucrosquamatus . In total, 16 polymorphic microsatellite loci were screened in 150 snakes (48 males, 44 females, 58 samples without sex information) covering most of their distribution. Microsatellite analysis revealed high genetic diversity in P . mucrosquamatus . Bayesian clustering of population assignment identified two major clusters for all populations, somewhat inconsistent with the mitochondrial DNA phylogeny of P . mucrosquamatus reported in previous research. Analyses based on 92 sex‐determined and 37 samples of P . mucrosquamatus from three small sites in Sichuan, China (Mingshan, Yibin, and Zizhong) consistently suggested female‐biased dispersal in P . mucrosquamatus, which is the first example of this pattern in snakes. The female‐biased dispersal patterns in P . mucrosquamatus may be explained by local resource competition. Abstract : In this study, we explored the genetic diversity and dispersal patterns of the widely distributed Asian pitviper Protobothrops mucrosquamatus . Microsatellite analysis revealed high genetic diversity in P . mucrosquamatus . Analyses based on sex‐determined samples suggested female‐biased dispersal in P . mucrosquamatus, which is the first example of this pattern in snakes. The female‐biased dispersal patterns in P . mucrosquamatus may be explained by local resource competition.